Respostas

2014-03-29T19:00:23-03:00
F(x) = 3x² + 5x - 12
3x² + 5x - 12 = 0
a = 3
b = 5
c = -12
          Δ = b² - 4ac           
          Δ = 5² - 4 . 3 . (-12)
          Δ = 25 + 144
          Δ = 169
                       x = - b ± √Δ
                                2a
                       x = - 5 ± √169
                                 2 . 3
                       x' = - 5 - 13 = -18 = -3
                                  6          6 
                       x'' = - 5 + 13 8 = 1,3
                                   6         6

Espero ter ajudado. Valeu!